The Effects of Water Availability on Mature Cocoa Plant - Yeedum, Ibrohem (1988)
In Malaysia cocoa is usually grown in areas where prolonged drought is absent in Malaysia. In order to increase cocoa acreages, it may be necessary to extend cocoa planting to the northern areas of the Peninsular Malaysia where prolonged dry period occurs for several months in a year. A study is therefore carried out to observe the effects of reduced water availability on growth and productivity of mature cocoa. The results of the experiments showed that flowering in cocoa is rot dependent on soil water availability. Mild water stress at 75 to 80 percent of available soil water for one month, reduced leaf water potential, but not the yield of mature cocoa. When the mild water stress was prolonged to two mnths, the effect was similar to that exposed to 30 to 70 percent of available soil water for shorter periods. Yields were reduced through an increase in percentage cherelle wilt which comes about from reduced photosynthate production. Water stressed condition results in highly negative leaf water potential which brings about stomatal closure and reduced photosynthesis. It can therefore be concluded that under conditions of reduced water availability, irrigation is necessary to maintain sufficient water supply to maintain plant growth and productivity of the cocoa plant at the optimum level. Irrigation however has to be managed to prevent over supply of water which also is deleterious to plant growth and productivity.